Public Employment Services under Decentralization: Evidence from a Natural Experiment - Lukas Mergele; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies whether the decentralization of public employment services (PES) increases job placements among the unemployed. Decentralizing PES has been a widely applied reform used by governments aiming to enhance their efficacy. However, economic theory is ambiguous about its effects, and empirical evidence has been scarce. Using a difference-in-differences design, we exploit unique within-country variation in decentralization provided by the partial devolution of German job centers in 2012. We find that decentralization reduces job placements by approximately 10%. Decentralized providers expand the use of public job creation schemes which diminish job seekers' reemployment prospects but shift costs to higher levels of government.
Keywords: H11; H75; I38; J48; J64; 330; decentralization; public employment services; job placements